2017
DOI: 10.3390/rs9080802
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometric Visualization Analysis for Night-Time Light Remote Sensing Research from 1991 to 2016

Abstract: Abstract:In this paper, we conducted a scientometric analysis based on the Night-Time Light (NTL) remote sensing related literature datasets retrieved from Science Citation Index Expanded and Social Science Citation Index in Web of Science core collection database. Using the methods of bibliometric and Social Network Analysis (SNA), we drew several conclusions: (1) NTL related studies have become a research hotspot, especially after 2011 when the second generation of NTL satellites, the Suomi National Polar-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 73 publications
(90 reference statements)
0
30
0
Order By: Relevance
“…A bibliometric analysis helps identify research gaps and directions in one certain area [49]. In recent years, studies have applied this method to evaluate the research trends of remote sensing and its application in different scientific fields [50][51][52]. For instance, Zhang et al [53] combined the new index (geographical impact factor) and traditional bibliometric methods to study the global research trends in remote sensing studies.…”
Section: Introductionmentioning
confidence: 99%
“…A bibliometric analysis helps identify research gaps and directions in one certain area [49]. In recent years, studies have applied this method to evaluate the research trends of remote sensing and its application in different scientific fields [50][51][52]. For instance, Zhang et al [53] combined the new index (geographical impact factor) and traditional bibliometric methods to study the global research trends in remote sensing studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared to ordinary remote sensing images, nighttime light remote sensing images can more accurately reflect human activities, and a large number of studies have shown that nighttime light is highly correlated with Gross Domestic Product(GDP). Therefore, nighttime light can also be used to characterize the level of socioeconomic development in a region [22][23][24]. However, it can be seen from the relevant literature that most nighttime light remote sensing data have been used to separately study urban expansion [25][26][27] or socioeconomic phenomena [24,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The metadata analysis, also called as bibliometric analysis, belongs to the field of scientometrics. The analysis has the advantages of data-driven characteristics, and being objective, complete and repeatable [75] .…”
Section: A Meta-analysis Of DL Applications In Smart Agriculturementioning
confidence: 99%